2019
DOI: 10.3390/catal9030298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Copper-Supported Titanium Oxide Nanotubes as Electrocatalyst for the Electrochemical Reduction of Carbon Oxide to Organics

Abstract: Carbon dioxide (CO2) is considered as the prime reason for the global warming effect and one of the useful ways to transform it into an array of valuable products is through electrochemical reduction of CO2 (ERC). This process requires an efficient electrocatalyst with high faradaic efficiency at low overpotential and enhanced reaction rate. Herein, we report an innovative way of reducing CO2 using copper-metal supported on titanium oxide nanotubes (TNT) electrocatalysts. The TNT support material was synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Hossain et al reported that the Cu/TiO 2 catalyst showed a very low methanol selectivity of 5% under −2.5 V vs NHE, while the catalyst showed higher selectivity toward CO and H 2 . The addition of TiO 2 nanotubes promoted CO 2 adsorption and stabilized the essential reaction intermediate and therefore afforded the Cu/TiO 2 catalyst a stable ECR process . To improve the ECR performance of copper-based catalysts, CuO and Cu 2 O had been doped with TiO 2 and ZnO, respectively. , The total FEs for alcohol products of CuO/TiO 2 and Cu 2 O/ZnO were 42.6 and 31.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hossain et al reported that the Cu/TiO 2 catalyst showed a very low methanol selectivity of 5% under −2.5 V vs NHE, while the catalyst showed higher selectivity toward CO and H 2 . The addition of TiO 2 nanotubes promoted CO 2 adsorption and stabilized the essential reaction intermediate and therefore afforded the Cu/TiO 2 catalyst a stable ECR process . To improve the ECR performance of copper-based catalysts, CuO and Cu 2 O had been doped with TiO 2 and ZnO, respectively. , The total FEs for alcohol products of CuO/TiO 2 and Cu 2 O/ZnO were 42.6 and 31.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All these peaks correlate well with the Joint Committee on Powder Diffraction standard (JCPDS No. 21-1272) for the TiO 2 anatase phase [ 29 , 30 , 31 ]. In general, in all of the prepared catalysts, the crystal structure was maintained after mono (Cu or Pd) and bimetallic (Cu-Pd) addition on the titanium oxide support, in any of the studied morphologies, was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a small peak at 2θ = 27.32°, in some cases, such as in the Cu/TNS catalyst, has been linked to rutile phase impurities as it corresponds to (110) crystal plane of rutile phase of titanium oxide (JCPDS Card no. 21-1276) [ 29 , 32 ]. In all of the herein prepared catalysts, a slight upshift was found in the main (101) 2θ value peak compared to pure TiO 2 ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding new types of active N sites can be insightful to increase the reduction efficiency. [20] Nitrogen-doped carbon materials can be produced from various carbon sources, [21][22][23][24] such as metal organic framework, macromolecular compound and small organic molecules, etc. Aniline polymers have attracted many attentions because of the environmental stability, high electrical conductivity, and redoxrelated characteristics of nitrogen.…”
Section: Introductionmentioning
confidence: 99%